Faktor Yang Memengaruhi Keputihan Pada Siswi Kelas XII Di Sekolah Menengah Atas Swasta Harapan Mekar Medan Tahun 2022 - Jessi Gustina; Razia Begum Suroyo; Jitasari Tarigan Sibero; Thomson P Nadapdap; Ivansri Ivansri (Jurnal Anestesi, 2023)
Adolescents should aware of leucorrhea symptoms. Continuous pathological vaginal discharge will disrupt the function of the female reproductive organs, especially in the ovarian tract, which can cause infertility. Women who lack knowledge and information about genital hygiene will also have an impact on their behavior in maintaining genital hygiene, because knowledge and good care behavior are determining factors in maintaining genital hygiene. This study aimed to determine and analyze the factors that influence leucorrhea in female students. This is quantitative and qualitative mixed methods research. The research was conducted at SMA Harapan Mekar Medan. The population was all class XII female students totaling 33 people. The sampling used was total sampling. Data analysis used univariate and bivariate analysis with chi-square test, and multivariate analysis with multiple logistic regression test at 95% confidence level (?=0.05). The results showed that the factors influencing leucorrhea in class XII female students at the School were knowledge (p=0.005), attitude (p=0.016), behavior (p=0.005), and source of information (p=0.006) and there was no effect of the adolescent care health program on leucorrhea (p=1.000).  The conclusion shows that knowledge of personal hygiene is the most dominant variable affecting leucorrhea in female students. It is suggested to the School to pay attention to facilities such as clean water sanitation and toilets and cooperate with the Health Center to organize health counseling and demonstrate how to take care of genital hygiene using a phantom of external reproductive organs so that students can directly practice genital hygiene actions